Analysis of youth professional orientation in the Republic of Croatia - Rafajac, Ozren (Array, 2019)
By using various scientific methods, including methods of survey (N=996) and methods of descriptive and inferential statistics, this research tries to explore how many young people in the Republic of Croatia need help in professional orientation and how they choose their professions. Given that only 21.9% of the respondents are completely confident in what their vocation will be, while 41.7% of them estimate they will have middle, low or very low ability to find jobs in occupations they have chosen. The research suggests that a large number of young people in the Republic of Croatia need services of professional orientation. The most important factors that motivate young people to choose a specific career are personal interest for that profession, opportunity to have fun, personal talent and an opportunity to meet new and interesting people. Interestingly, a good salary, possibility to travel and opportunity for a fast employment are only partially important factors. Although the Croatian educational system provides a satisfactory level of preparation in both, theoretical knowledge and practical skills relevant to the professions that young people want to deal with, the conducted research suggests there is a place for substantial improvements, especially in vocational education and training (VET) services that support more opportunities for learning of practical skills.